Structure of a Clostridium botulinum C143S thiaminase I/thiamin complex reveals active site architecture, - Sikowitz, Megan D. (2013)
Thiaminases are responsible for the degradation of thiamin and its metabolites. Two classes of thiaminases have been identified based on their three-dimensional structures and in their requirements for a nucleophilic second substrate. While the reactions of several thiaminases have been characterized, the physiological role of thiamin degradation is not fully understood. We have determined the three-dimensional X-ray structure of an inactive C143S mutant of Clostridium botulinum (Cb) thiaminase I with bound thiamin at 2.2 Å resolution. The C143S/thiamin complex provides atomic level details of the orientation of thiamin upon binding to Cb-thiaminase I and the identity of active site residues involved in substrate binding and catalysis. The specific roles of active site residues were probed using site directed mutagenesis and kinetic analyses, leading to a detailed mechanism for Cb-thiaminase I. The structure of Cb-thiaminase I is also compared to the functionally similar but structurally distinct thiaminase II.